Economic Activities in Riverbanks Community Settlement in Benua Anyar Village - Muhammad Adhitya Hidayat Putra; Herry Porda Nugroho Putro; Syaharuddin Syaharuddin; Muhammad Rezky Noor Handy; M. Ridha Ilhami; Nona Ayuriszki; Muhammad Risalan Uzhma (Social Studies Conference Proceedings, 2022)
The riverside area is an area where there are also many residential areas around it. Usually, a group living on the river's banks is called a riverbank community. This research process used a qualitative approach to the type of case study research. The research was conducted in the Banua Anyar sub-district, with the research subjects being the Banua Anyar sub-district community. Continental Anyar Village is a culinary tourism village in terms of carrying out economic activities. With the development of culinary tourism, it is assumed that it can bring changes to the socio-economic sector, especially the small and informal economic sectors. The existence of small traders, souvenir traders, typical restaurants, and so on will bring socio-economic changes. The results of this study show that Banua Anyar, as a culinary area, offers many restaurants and food stalls serving Banjar specialties. Not only typical of Banjar, but the primary food is also widely available in the Banua Anyar sub-district area. The people living in the Banua Anyar sub-district carry out many economic activities, namely processing and producing goods, distributing goods, and consuming goods traded in the Banua Anyar sub-district.